(untitled) (Circe de clásicos y modernos, 2020)
Socially, we usually associate values or abili-ties with different animals, and this representation takes its roots in several literary genres in classical antiquity. In this paper, we analyze comparatively the configuration of donkey as characters in a corpus of Phaedrus’ fables (1. 15, 1. 29, 2. 7 y 3. 6) and passages from the novel The Golden Ass of Apuleius (4. 5-4. 6, 7. 16-7. 23, 8. 23-8. 30) in order to address what fable and satire procedures present in Phaedrus’ fables are resignified in Lucio’s hybrid configuration (character and storyteller) as donkey and human.